USE OF FACEBOOK AS AN EDUCATIONAL TOOL - Ngoyi, Luka; Siuluta, Mwasile Niza; Muwamba, Jerry; Banda, Daliso; Hatilima, Jasper; Ngoyi, Abraham; Mpanga, Shadreck (IJRDO-Journal of Applied Science, 2015)
Technology is ubiquitous, embracing almost every part of our lives, our communitiesand our homes. In the field of education technology doesn’t have a secondary role in the soleprocess of knowledge transferring especially because technology is becoming increasinglyintegrated into the lives of learners of all ages and groups. In particular of this technology is theuse of Facebook as an education tool. Originally designed for college students in the UnitedStates in 2004, Facebook was created as a social networking website. Facebook later expandedto different educational settings. Facebook allows each user to create a profile, updating it withpersonal information such as home address, mobile phone number, interesting religious viewsand also allows people to form groups and post pictures. Today with approximately 800 millionsubscribers worldwide (according to www.internetworldstats.com), Facebook now has adiverse community of users at all levels of education and areas of society including companiesand universities. This number of users all around the globe makes Facebook the most usedsocial network out there. This has made Facebook to be integrated into the way teachers,lecturers and professors teach and administer courses. But like always, the use of Facebook aseducational tool has been received with mixed feelings, concerns related to privacy and anxietyin the interaction with professors in this environment, a belief that doesn’t serve an academicpurpose and the opinion that facility should simply avoid “education appropriation” thesebackstage social space have been expressed. Yet other people have supported the notion ofusing Facebook as an education tool, as survey worldwide has shown